Performance of Dye-Sensitized Solar Cell Utilizing the Extract of Cassava (Manihot Esculenta) Leaves, Guava (Psidium Guajava) Leaves, and Mango (Mangifera Indica) Leaves - Kathleen E. Espina; Alberto D. Yazon; Karen D. Manaig; Sherwin B. Sapin; Lerma P. Buenvinida (Journal of Healthcare and Biomedical Science, 2024)
Dye- sensitized solar cell (DSSC) is a third-generation solar cells that utilize natural dyes from leaves extract to absorb sunlight and generate electricity. This study aimed to investigate the performance of DSSCs using the leaf extracts of cassava, guava, and mango as natural dyes in terms of UV-Vis absorption and energy output. The experimental method was applied in which the researcher constructed three DSSCs, with each treatment involving the same fabrication and construction. The UV-Vis Spectrum peak value and UV absorption was obtained from UV-Vis Analysis. A multimeter was used to record each voltage to determine the energy output produced by the DSSCs and the commercial solar cell. One-way ANOVA was used to determine the significant difference in the UV absorption of the natural dyes. To determine the significant difference between the three treatments and control in pairwise comparison in terms of energy output, One-Way ANOVA Analysis and Post Hoc Tukey were used. The results showed no significant difference in UV absorption among the three natural dyes. This result signified that the same pigment content gave almost the same UV absorbance at a common UV spectrum peak wavelength. DSSCs with natural dyes produce less electrical energy than commercial solar cells. There was a significant difference in the energy output between the three treatments and the control. DSSCs utilizing natural dyes produced electrical energy in smaller amounts.